Analisis Tingkat Kesehatan Bank Bumn Di Daftar Bursa Efek Indonesia Dengan Metode Rgec (Risk Profile, Good Corporate Governance, Earnings, Capital) Periode 2021-2022 - Abd. Hafidh Ali; Arini Nur Fadilah (Program Studi Akuntansi Syari'ah Universitas Ibrahimy, 2024)
A activities that requires its existence in the economic world is the business activities of banking financial institutions. The level of bank health is very important for the formation of trust in the banking industry. BUMN is the object of this research because BUMN Banks are the dominant business players in developing countries, including Indonesia. Seeing the very large role of state-owned banks in the Indonesian economy, it is hoped that state-owned banks will be able to compete by continuing to maintain their health so that they will have a positive influence on the national economy as a whole. The focus of the research is the health level of state-owned banks listed on the Indonesia Stock Exchange in 2021 and 2022 using the RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) method. The data used in this research is secondary data with data sources from the Indonesian Stock Exchange. The type of research used is non-experimental quantitative descriptive research. The data collection techniques used are documentation techniques and literature study. Rating the health level of state-owned banks using the Risk Profile, Good Corporate Governance, Earnings, Capital or (RGEC) method shows that the health ranking of BRI, BNI, BSI and Bank Mandiri in 2021-2022 is at Composite Rank 1 (PK-1) with the title